Cryopreservation of Animals and Cryonics: Current Technical Progress, Difficulties and Possible Research Directions - Ekpo, Marlene Davis; Boafo, George Frimpong; Gambo, Suleiman Shafiu; Hu, Yuying; Liu, Xiangjian; Xie, Jingxian; Tan, Songwen (Frontiers in Veterinary Science, 2022)
The basis of cryonics or medical cryopreservation is to safely store a legally dead subject until a time in the future when technology and medicine will permit reanimation after eliminating the disease or cause of death. Death has been debunked as an event occurring after cardiac arrest to a process where interjecting its progression can allow for reversal when feasible. Cryonics technology artificially halts further damages and injury by restoring respiration and blood circulation, and rapidly reducing temperature. The body can then be preserved at this extremely low temperature until the need for reanimation. Presently, the area has attracted numerous scientific contributions and advancement but the practice is still flooded with challenges. This paper presents the current progression in cryonics research. We also discuss obstacles to success in the field, and identify the possible solutions and future research directions.